Knowledge about, attitude toward, and practice of complementary and alternative medicine among nursing students: A systematic review of cross-sectional studies - Zhao, Fei-Yi; Kennedy, Gerard A.; Cleary, Sonja; Conduit, Russell; Zhang, Wen-Jing; Fu, Qiang-Qiang; Zheng, Zhen (Frontiers in Public Health, 2022)
Background The globally growing demand for complementary and alternative medicine (CAM) has attracted educators' attention to integrate CAM into conventional nursing programs. This systematic review aimed to understand the status quo of nursing students (NSs)' overall rated knowledge of, attitude/belief toward, and practice/previous use or experience (KAP) of CAM in surveys, given these factors may influence NSs' receptivity to CAM curricula, and may be of value in guiding the development of effective teaching strategies. Methods Formally published cross-sectional quantitative studies investigating the primary outcome of KAP toward CAM by NSs were searched for from eight databases from their inception through to 28 April 2022. PRISMA 2020 guidelines were followed. Results Twenty-six studies were included for analysis, 25 of which were judged to be of moderate to high quality. Despite limited and poorly informed knowledge of CAM therapies, the majority of NSs generally viewed them in a positive light. Furthermore, NSs usually reported an interest in further learning, and supported and welcomed the integration of CAM curricula, at least as elective modules, into existing nursing programs. Lack of evidence was perceived as a major barrier to the use or integration of CAM. Mass media and the internet were the main sources via which NSs access CAM information. Measurement of KAP in all included studies was via self-designed questionnaires/scales or adapted from previously developed questionnaires/scales. Conclusions The need for integrating and strengthening CAM curricula into current nursing education is identified. Besides theoretical knowledge and matched clinical placement, skills training in literature searching and evidence-based practice are advised to be included in the curricula design. The experiential learning mode is strongly recommended for delivering specific CAM modalities. In addition, a standard instrumentation for determining NSs' KAP toward CAM should be designed and examined for use in different cultural settings. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=300602, identifier: PROSPERO CRD42022300602.